Courts, cabinet and coalition parties: The politics of euthanasia in a parliamentary setting - Steunenberg, Bernard (British journal of political science, 1997)
An analysis is made of the interaction between the legislature and the judiciary in the Dutch parliamentary setting, focusing in particular on the issue of euthanasia. Using the methodology of positive political theory, two alternative hypotheses are derived about the extent to which the courts may affect public policies. Two main conclusions can be drawn from the analysis of the decision-making process on euthanasia. First, the statutory interpretation the courts gave on euthanasia in the 1980s supports the hypothesis of the court as a policy advocate, not a policy conserver. Secondly, the fact that the courts were able to introduce and maintain a more liberal interpretation of euthanasia during the last decade can be explained as a consequence of the heterogenous preferences on this issue held by the political parties that formed the successive governing coalitions. (British Journal of Political Science / FUB)